Fundamentals of Digital and Computer Design with VHDL - Sandige, Richard S.; Sandige, Michael L. (New York, N.Y. : Mcgraw-Hill, 2012)
Provides an introductory course in digital design and computer design. This book focuses on digital design, computer design and assembly language programming. It is suitable for students of electrical engineering, computer engineering and computer science.
1: Boolean Algebra, Boolean Functions, VHDL, and Gates 2: Number Conversions, Codes, and Function Minimization 3: Introduction to Logic Circuit Analysis and Design 4: Combinational Logic Circuit Design with VHDL 5: Bistable Memory Device Design with VHDL 6: Simple Finite State Machine Design with VHDL 7: Computer Circuits 8: Circuit Implementation Techniques 9: Complex Finite State Machine Design with VHD 10: Basic Computer Architectures 11: Assembly Language Programming for VBC1 12: Designing Input/Output Circuits 13: Designing Instruction Memor Loading Program Counter, and Debounced Circuit 14: Designing Multiplexed Display Systems 15: Designing Instruction Decoders 16: Designing Arithmetic Logic Units 17: Completing the Design for VBC1 18: Assembly Language Programming for VBC1-E 19: Designing Input/Output Circuits for VBC1-E 20: Designing the Data Memory Circuit for VBC1-E 21: Designing th Arithmetic, Logic, Shift, Rotate, and Unconditional Jump Circuits for VBC1-E 22: Designing a Circuit to Prevent Program Execution During Manual Loading for VBC1-E 23: Designing Extented Instruction Memory for VBC1-E 24: Designin the Software Interrupt Circuits for VBC1-E 25: Completing the Design for VBC1-E Appendices.
Keywords: VHDL (Hardware description language); VHDL